Effect of bubble size and velocity on collision efficiency in chalcopyrite flotation - Hassanzadeh, Ahmad; Hassas, Behzad Vaziri; Kouachi, Sabri; Brabcova, Zuzana; Çelik, Mehmet S. (Elsevier BV, 2016)
In flotation processes, bubble diameter (db), bubble velocity (vb), and turbulence are the key factors involved in particle-bubble interactions. The collision efficiency (EC) is used as an indicator to assess the extent of these interactions. In this work, the bubble surface is assumed mobile with potential flow conditions dominating the particle-bubble collision efficiency. The collision probability has been determined by Schulze and Generalized Sutherland Equation (GSE) models in the particle size range of 1–100 μm. Bubble diameters of 0.08, 0.12, and 0.15 cm and bubble velocities of 10, 20 and 30 cm/s were selected to study the flotation of chalcopyrite. The results reveal that the collision efficiency of ultra-fine particles (1–10 μm) is generally improved with bubbles of finer sizes, e.g. db = 0.08 cm compared to those of larger sizes, i.e. db = 0.12 and db = 0.15 cm. Also, in the same particle size range, EC decreases with increasing the bubble velocity. The best agreement between Schulze and GSE models for ultra-fine particles at all bubble sizes is achieved at the bubble velocity of 30 cm/s. The maximum EC of chalcopyrite (0.12) using the GSE model is found to occur for coarser particles of 70–100 μm in size at bubble conditions of vb = 30 cm/s and db = 0.12 cm. Results reveal that for a given bubble diameter increasing the bubble velocity from 10 to 30 cm/s makes the inertial force more effective on finer particles. A detailed interpretation of the effect of bubble diameter and its velocity on particle-bubble interaction of chalcopyrite is discussed from a theoretical point of view.